Strategic information system planning (SISP) in private universities in Malaysia: An exploratory study - Yaakub, Nor Asiah; Mat Saat, Rafeah; Raja Mohd Ali, Raja Haslinda (Universiti Utara Malaysia, 2005)
Strategic Information System Planning (SISP) is a process whereby an organization determines a portfolio of computer-based application to help in achieving business objectives. Thus, SISP plays an important role in assisting the managers to determine the new information system (IS) and information technology (IT) strategies, allocate resources, position suitable applications and gaining competitive advantage. Today, it is undeniable that the businesses of education sectors are also relying heavily on the effectiveness of SISP. Therefore, this study is primarily focused on the business of the education sector. It is conducted to identify the extant of SISP practices in private universities in Malaysia. Data are gathered through survey and analyzed using descriptive analysis. Result has shown that only 16.7 percent of the respondents implemented SISP. Factors such as failing to get top management support, not having a clear-cut corporate plan and unable to obtain sufficient1 y qualified personnel are reasons for not implementing SISP in their business. Nevertheless all respondents strongly agreed that IS are very important to their organization.